2016
DOI: 10.1111/jedm.12100
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Computerized Adaptive Testing: From Group Sequential Design to Fully Sequential Design

Abstract: Computerized adaptive testing (CAT) and multistage testing (MST) have become two of the most popular modes in large-scale computer-based sequential testing. Though most designs of CAT and MST exhibit strength and weakness in recent largescale implementations, there is no simple answer to the question of which design is better because different modes may fit different practical situations. This article proposes a hybrid adaptive framework to combine both CAT and MST, inspired by an analysis of the history of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(48 reference statements)
0
21
0
1
Order By: Relevance
“…To address the aforementioned challenges, this study aims to propose a series of flexible CAT (FCAT) designs based on the SICM model. These FCAT designs are motivated by a hybrid adaptive framework proposed by S. Wang et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…To address the aforementioned challenges, this study aims to propose a series of flexible CAT (FCAT) designs based on the SICM model. These FCAT designs are motivated by a hybrid adaptive framework proposed by S. Wang et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…The item selection is performed automatically, but all stages of questions can be reviewed before administration (Chang, 2014). Wang et al (2016) suggest to ask a group of questions at the beginning of the test, when little information about learner ability is available, and progressively reduce the number of questions of each stage in order to increase opportunities to adapt. Also, asking questions in pools means that we can do content balancing at each stage, instead of jumping from one knowledge component to the other after every question.…”
Section: Multistage Testingmentioning
confidence: 99%
“…Adaptive testing is a modern assessment method, which tailors the test based on each examinee's ability estimate and can make sure that each selected item provides as much information as possible for estimating the examinees’ ability (S. Wang, Lin, Chang, & Douglas, ). Compared with the traditional paper‐and‐pencil testing (P&P), adaptive testing is more efficient and the test length is much shorter without loss of measurement accuracy (Wainer & Eignor, ).…”
mentioning
confidence: 99%
“…Zheng and Chang () called the MST that incorporates on‐the‐fly assembly strategies as the on‐the‐fly assembled multistage adaptive testing (OMST). Research (S. Wang et al., ; Zenisky, ; Zheng, Nozawa, Gao, & Chang, ) has indicated that MST has many advantages over CAT: first, MST adapts between stages but not within each stage, therefore examinees are allowed to navigate back and forth within current stage to review and change the answers which will make examinees feel less anxiety (Zenisky, ); second, MST allows test developers to adjust the number of stages and the module length assignment according to different situations; third, the nonstatistical constraints can be satisfied with ease in MST (Zheng et al, ). Due to these benefits, many high‐stakes tests have switched from the CAT mode to the MST mode (S. Wang et al, ).…”
mentioning
confidence: 99%